P62 functions as a signal hub in metal carcinogenesis. (November 2021) - Zhang, Zhuo; Costa, Max
Abstract: A number of metals are toxic and carcinogenic to humans. Reactive oxygen species (ROS) play an important role in metal carcinogenesis. Oxidative stress acts as the converging point among various stressors with ROS being the main intracellular signal transducer. In metal-transformed cells, persistent expression of p62 and erythroid 2–related factor 2 (Nrf2) result in apoptosis resistance, angiogenesis, inflammatory microenvironment, and metabolic reprogramming, contributing to overall mechanism of metal carcinogenesis. Autophagy, a conserved intracellular process, maintains cellular homeostasis by facilitating the turnover of protein aggregates, cellular debris, and damaged organelles. In addition to being a substrate of autophagy, p62 is also a crucial molecule in a myriad of cellular functions and in molecular events, which include oxidative stress, inflammation, apoptosis, cell proliferation, metabolic reprogramming, that modulate cell survival and tumor growth. The multiple functions of p62 are appreciated by its ability to interact with several key components involved in various oncogenic pathways. This review summarizes the current knowledge and progress in studies of p62 and metal carcinogenesis with emphasis on oncogenic pathways related to oxidative stress, inflammation, apoptosis, and metabolic reprogramming.